2010
DOI: 10.1073/pnas.1000395107
|View full text |Cite
|
Sign up to set email alerts
|

Brain diversity evolves via differences in patterning

Abstract: Differences in brain region size among species are thought to arise late in development via adaptive control over neurogenesis, as cells of previously patterned compartments proliferate, die, and/or differentiate into neurons. Here we investigate comparative brain development in ecologically distinct cichlid fishes from Lake Malawi and demonstrate that brains vary among recently evolved lineages because of early patterning. Divergence among rock-dwellers and sand-dwellers in the relative size of the telencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 34 publications
5
125
1
Order By: Relevance
“…In the retina, however, a lower Six3.2 activity would not be sufficient to repress Rx3, the activation of which would consequently repress Foxg1-mediated telencephalic fate, as previously suggested (Kennedy et al, 2004;Stigloher et al, 2006). In support of this hypothesis, a recent study has shown that differences in the extent of the Six3 expression domain positively correlate with the size of the telencephalon in cichlid fishes (Sylvester et al, 2010 compatible with studies of other Six3 orthologues showing that activator and repressor roles depend on context-specific interactions. Indeed, Six3 binds a variety of proteins, including other TFs (Tessmar et al, 2002), transcriptional co-repressors of the Groucho family (Kobayashi et al, 2001;Lopez-Rios et al, 2003), coactivators such as EYA4 (Abe et al, 2009) and components of the chromatin remodelling complexes, including MTA1 and HDAC2 (Manavathi et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the retina, however, a lower Six3.2 activity would not be sufficient to repress Rx3, the activation of which would consequently repress Foxg1-mediated telencephalic fate, as previously suggested (Kennedy et al, 2004;Stigloher et al, 2006). In support of this hypothesis, a recent study has shown that differences in the extent of the Six3 expression domain positively correlate with the size of the telencephalon in cichlid fishes (Sylvester et al, 2010 compatible with studies of other Six3 orthologues showing that activator and repressor roles depend on context-specific interactions. Indeed, Six3 binds a variety of proteins, including other TFs (Tessmar et al, 2002), transcriptional co-repressors of the Groucho family (Kobayashi et al, 2001;Lopez-Rios et al, 2003), coactivators such as EYA4 (Abe et al, 2009) and components of the chromatin remodelling complexes, including MTA1 and HDAC2 (Manavathi et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…In the retina, however, a lower Six3.2 activity would not be sufficient to repress Rx3, the activation of which would consequently repress Foxg1-mediated telencephalic fate, as previously suggested (Kennedy et al, 2004;Stigloher et al, 2006). In support of this hypothesis, a recent study has shown that differences in the extent of the Six3 expression domain positively correlate with the size of the telencephalon in cichlid fishes (Sylvester et al, 2010 (Tessmar et al, 2002), transcriptional co-repressors of the Groucho family (Kobayashi et al, 2001;Lopez-Rios et al, 2003), coactivators such as EYA4 (Abe et al, 2009) and components of the chromatin remodelling complexes, including MTA1 and HDAC2 (Manavathi et al, 2007).Second, our results show that the medaka Six3 paralogues have undergone at least partial subfunctionalisation, with a major function for Six3.1 in the eye and significant involvement of Six3.2 in telencephalon formation. Six3.2 gain-of-function did not induce the formation of ectopic retinal tissue, in contrast to the effect of Six3.1 overexpression (Loosli et al, 1999;Lopez-Rios et al, 2003), but rather appeared to recruit proliferating progenitors into the telencephalic domain.…”
supporting
confidence: 60%
“…Thus, their repositioning would not only alter the location of individual neuronal populations, but would also allow new combinations of genes to be co-expressed and thus create novel neuronal subtypes and circuits. In fact, such a mechanism has been demonstrated in recently diverged species of cichlid fish, where changes in Wnt regulation and activity can mimic changes in forebrain structure between species (Sylvester et al, 2010).…”
Section: Box 2 Modular Changes In Hypothalamic Anatomy: a Means To Ementioning
confidence: 99%
“…Similarly, other scientists have shown that, among a group of teleost fishes, adult differences in the size of specific forebrain areas correlate with species differences in the expression of genes involved in forebrain patterning. Indeed, manipulating the expression of these genes can recreate (i.e., phenocopy) some of the adult species differences (Sylvester et al, 2010). What remains unknown in these studies is the molecular cause of the species differences in embryonic gene expression.…”
Section: Monographmentioning
confidence: 99%